Overexpression of the Neuritotrophic Cytokine S100β Precedes the Appearance of Neuritic β-Amyloid Plaques in APPV717F Mice - Sheng, J. G. (2000)
Homozygous APPV717F transgenic mice overexpress a human β-amyloid precursor protein (βAPP) mini-gene encoding a familial Alzheimer’s disease mutation. These mice develop Alzheimer-type neuritic β-amyloid plaques surrounded by astrocytes. S100β is an astrocyte-derived cytokine that promotes neurite growth and promotes excessive expression of βAPP. S100β overexpression in Alzheimer’s disease correlates with the proliferation of βAPP-immunoreactive neurites in β-amyloid plaques. We found age-related increases in tissue levels of both βAPP and S100β mRNA in transgenic mice. Neuronal βAPP overexpression was found in cell somas in young mice, whereas older mice showed βAPP overexpression in dystrophic neurites in plaques. These age-related changes were accompanied by progressive increases in S100β expression, as determined by S100β load (percent immunoreactive area). These increases were evident as early as 1 and 2 months of age, months before the appearance of β-amyloid deposits in these mice. Such precocious astrocyte activation and S100β overexpression are similar to our earlier findings in Down’s syndrome. Accelerated age-related overexpression of S100β may interact with age-associated overexpression of mutant βAPP in transgenic mice to promote development of Alzheimer-like neuropathological changes.